2015
DOI: 10.1089/apc.2015.0146
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Dynamics and Sexual Risk Reduction Strategies Among Heterosexual Young Adults: A Qualitative Study of Sexually Transmitted Infection Clinic Attendees at an Urban Chicago Health Center

Abstract: Few studies have examined risk-reduction alternatives to consistent condom use for HIV prevention among heterosexual young adults. We used qualitative methodology to explore risk reduction strategies and contextual factors influencing attempts to reduce risk in an urban, high morbidity sexually transmitted infection (STI) clinic. Focus groups were conducted October-December 2014 with heterosexually identified men (n = 13) and women (n = 20) aged 18-29 seeking STI screening at an urban clinic. Groups were audio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…However, it is known that young women living with HIV engage in unprotected intercourse and use condoms inconsistently. 16,17 It is also known that unprotected vaginal and anal intercourse is related to young women's overall self-efficacy, self-efficacy to discuss safer sex with one's partner and self-efficacy to refuse safe sex 16 and that behavioral interventions targeted to adolescents have the ability increase condom use and decrease overall number of sexual partners. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that young women living with HIV engage in unprotected intercourse and use condoms inconsistently. 16,17 It is also known that unprotected vaginal and anal intercourse is related to young women's overall self-efficacy, self-efficacy to discuss safer sex with one's partner and self-efficacy to refuse safe sex 16 and that behavioral interventions targeted to adolescents have the ability increase condom use and decrease overall number of sexual partners. …”
Section: Discussionmentioning
confidence: 99%
“…2,17,19 A little over half of the young women in the trial did not report any vaginal intercourse in the 3 months prior to baseline and 25% reported having no male sexual partners in the last 3 months. In contrast to our preliminary study where young women reported multiple sexual partners, 2 the mean number of male sexual partners in the last 3 months was 1.48 and 1.24 among the intervention and control group, respectively.…”
Section: Brothers Et Almentioning
confidence: 99%
“…In order to grasps factors that influence the development of sexual scripts for YSSAAW, we must explore cultural, societal and life experiences that contribute to the development of what are normal to them, specifically normal sexual behaviors. Cultural esteem gained by maintaining a heterosexual relationship with a man within the AA community is highly valued and often leads women to focus on benefits of relationships (i.e., stability, finances, family) and to ignore costs by male partners that often include infidelity [86], concurrency that is rarely discussed within partnerships, and interference with safer sexual decisions stemming from frequent alcohol and substance use [87]. Specifically, sexual scripts of YSSAAW are more likely to involve riskier sexual behaviors than scripts of other/ older AA women.…”
Section: Introductionmentioning
confidence: 99%
“…Much still needs to be learned about the accounts provided by heterosexuals for unprotected sex although there are some data about the typical challenges they perceive regarding consistent condom use. In a focus group study of 33 heterosexual men and women from Chicago, 23 participants said that typical reasons for their engaging in unprotected sex with casual partners were alcohol use, because asking for condoms could be perceived as a lack of trust in a partner, and because conversations about HIV/STI testing and safer sex occurred too close to the moment of sex when, in the heat of the moment, it was easy to make an impulsive decision.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common explanations women offered for having engaged in casual sex is that alcohol was responsible for lowering their inhibitions and making them behave atypically. 23,29,36 People have also blamed casual unprotected sex on the symbolic significance of condoms; that is, women have suggested that they avoided carrying condoms because they connote promiscuity or because asking for their use could signify that they expect the encounter to be a one-night stand. 26,[37][38][39] Heterosexual men in some studies have also expressed that they only feel the need to use condoms with casual female partners, especially ones who seem very sexually active, and that it is harder to request a main partner to use condoms without being accused of cheating.…”
Section: Introductionmentioning
confidence: 99%